Factors Influencing Nurses’ Compliance Level in the Application of Hand Hygiene in Inpatient Wards of Muntilan General Hospital - Andika Dwi Rianita; Dyah Suryani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
Infectious diseases are still the leading cause of morbidity and mortality in the world. One of the infections was a nosocomial infection. Nurses have appreciable influence regarding nosocomial infection incident because nurses have a great deal of interaction with the patient during 24 hours. The prevention of nosocomial infection can be conducted by a nurse is with hand hygiene practice. The purpose of this research is to know factors influencing nurses’ compliance level in the application of hand hygiene at in inpatient ward of Muntilan General Hospital. This was a quantitative research with research design cross-sectional. The sampling technique used was the Proportionate Stratified Random Sampling with the number of respondents was 54 nurses. The instrument of the research applied a questionnaire and checklist. Analyses of the data used were the Chi-Square test. This research indicated there was a correlation between motivation with a compliance level of nurses in application of hand hygiene (p-value 0.000<0,05).There was a correlation between attitudes with a compliance level of nurses in application of hand hygiene (p-value 0.000<0,05).There was no correlation between work period with a compliance level of nurses in application of hand hygiene in of Muntilan General Hospital (p-value 0.459>0,05).